Fig freezing in sugar solutions : quality, phenolics composition and sensory properties during storage - Levaj, Branka (Array, 2021)
The effect of fig freezing in sugar solution on fig"s quality and sensory traits as well as phenolic content during storage was examined. Fresh figs were frozen without any treatment (control - CON), in sucrose solution (30%) (SUC) and sucrose solution (30%) with ascorbic acid (2%) (SUCAA), and stored at -18 ⁰C for 210 days. Samples were analyzed every seventy days for pH, total soluble solids (TSS), sugars and phenolics composition, skin and pulp color, and they were sensorially evaluated. According to ANOVA, storage time showed significant impact on more analyzed parameters than freezing conditions. CON and SUC had the highest TSS, what was also sensorially detected. SUCAA was evaluated with the lowest scores for sweetness and typical fig flavor followed by the highest score for off-taste, off-flavor and off-odor. Contrary to TSS, individual sugars and phenolics were the lowest in CON. SUCAA showed the most brightener skin and the reddest pulp measured by colorimeter, and sensorially it obtained the highest scores for skin and pulp color. Storage time caused TSS and pH decrease, what reflected sensorially as a decrease of fig taste and flavor, as well as the appearance of off-taste, off-flavor and off-odor was also observed. Contrary, individual sugars and phenolics showed increase during storage, and the lowest amounts were present in CON. In conclusion, after 140 days all figs noticeably lost their desirable attributes, where CON fig was sensorially the best evaluated and SUCAA gained the lowest scores.